Control Of Corruption In Moderating The Effect Of Per Capita Income And Shadow Economy On Tax Revenue - Bhuana, Bhima Chandra; Wijaya, Suparna (Educoretax, 2024)
The less optimal tax revenue, the low level of income, the large proportion of shadow economy in the economies and the high level of corruption are problems for development. This study tries to revisit the linkage of these four development problems, and find out how corruption control conducted by the government can strengthen or weaken the impact of per capita income and shadow economy activities on tax revenue. A dataset of eighteen countries in the South Asia and Asia-Pacific region from 2002 to 2017 is analyzed using panel data regression. It was found that per capita income and government efforts to control corruption significantly have a positive effect on tax revenue, while the shadow economy significantly has a negative effect on tax revenue. Furthermore, as a moderating variable, government efforts to control corruption can significantly reduce the negative effect of the shadow economy on tax revenue. This finding suggests the urgency of controlling corruption by the government to optimize tax revenue, thereby overcoming development problems.